Common fixed point theorems of contractive-type mappings - Hee Soo Park; Jeong Sheok Ume (International Journal of Mathematics and Mathematical Sciences)
Using the concept of D-metric we prove some common fixed point theorems for generalized contractive mappings on a complete D-metric space. Our results extend, improve, and unify results of Fisher and Ćirić.